Comparison of the Short-Term Outcomes after Primary Anastomosis between an Emergency Operation with Manual Fecal Decompression in Completely Obstructed Left-Sided Colorectal Cancer and Non-Obstructed Colorectal Cancer in Elective Bowel Preparation: A Retrospective Single Center Study - Prasongdee, Rakkiat (The Thai Journal of Surgery, 2023)
Background: There are several emergency surgical methods for completely obstructed colorectal cancer, such as colostomy, tumor resection with Hartmann's procedure, or primary anastomosis with table lavage, sometimes adding protective ostomy. This treatment depends on the patient's condition and the surgeon's experience. As a result, patients need to undergo more than one operation. Therefore, if the effects of emergency surgery combined with manual fecal decompression and primary anastomosis are as effective as elective surgery, it will reduce patient complications. Objective: To compare the short-term outcomes after primary anastomosis between an emergency operation with manual fecal decompression in completely obstructed left-sided colorectal cancer and non-obstructed colorectal cancer in elective bowel preparation. Methods: A retrospective study comparing the short-term outcomes after primary anastomosis in completely obstructed left-sided colorectal cancer between an emergency operation with manual fecal decompression and elective bowel preparation in non-obstructed left-sided colorectal cancer in Buriram Hospital from 2009-2023. Short-term outcomes were analyzed, including anastomotic leak, surgical site infection, hospital stay, Dindo-Clavien classification, readmission, and mortality within 30 days after the operation. Given a statistically significant difference of p-value < 0.05. Results: There were 105 left-sided colorectal cancer patients, 52 men and 53 women. Emergency surgery, manual fecal decompression, and primary anastomosis 49 cases (46.7%), and elective surgery 56 cases (53.3%). There was no statistically significant in postoperative complication, Dindo-Clavien classification, and mortality in 30 days (p-value > 0.05). None of the patients had to be hospitalized within 30 days. Risk factors for complications were age ≥ 60 and preoperative comorbidity. Conclusion: Emergency surgery for completely obstructed left-sided colorectal cancer with manual fecal decompression and primary anastomosis is as effective as the short-term outcomes in elective bowel preparation surgery for non-obstructed left-sided colorectal cancer.